Literary Creative Process and Stylistic Exploration of Lyrical Prose Based on the Project-Based Learning Model - Didin Sahidin; Aditya Ansor Alsunah (UIN Raden Mas Said Surakarta, Indonesia, 2026)
Project-Based Learning (PjBL) has been widely recognized as an innovative instructional model that promotes active learning and creative production. However, its application in the teaching of lyrical prose writing is still limited. This study aims to examine the quality of literary creative processes and stylistic exploration in lyrical prose writing through the Project-Based Learning model. This study uses an evaluative descriptive design with a quantitative pre-experimental approach (one-group pretest-posttest design). Data were collected through a writing test (pretest and posttest) and continuous observation of student involvement during the project phases, complemented by a documentation technique analyzing the stylistic layers of the student-generated drafts. Data analysis techniques used are descriptive statistical analysis and inferential statistical analysis using the paired sample t-test, integrated with qualitative stylistic text interpretation. The aesthetic quality assessment of the text focuses on stylistic indicators, including diction, figurative language, imagery, structural coherence, and expressive depth. The results of the study show that the implementation of Project-Based Learning significantly improves the quality of lyrical prose writing, especially in the use of poetic language, originality of expression, and aesthetic coherence. In addition, the project-oriented approach is able to encourage active engagement, reflective thinking, and creative exploration during the writing process. These findings confirm that Project-Based Learning is an effective instructional model to facilitate lyrical prose writing and support the development of aesthetic and creative competencies in literary learning. Project-Based Learning (PjBL) telah diakui secara luas sebagai model pembelajaran inovatif yang mendorong pembelajaran aktif dan menghasilkan karya kreatif. Namun, penerapannya dalam pembelajaran menulis prosa liris masih relatif terbatas. Penelitian ini bertujuan untuk mengkaji kualitas proses kreatif sastra dan eksplorasi stilistika dalam penulisan prosa liris melalui model Project-Based Learning. Penelitian ini menggunakan desain deskriptif evaluatif dengan pendekatan kuantitatif praeksperimental (one-group pretest-posttest design). Data dikumpulkan melalui teknik tes (kemampuan awal dan kemampuan akhir), teknik observasi terhadap keterlibatan dalam proses kreatif, serta teknik dokumentasi berupa draf karya prosa liris mahasiswa. Teknik analisis data yang digunakan meliputi analisis statistik deskriptif dan analisis statistik inferensial menggunakan paired sample t-test yang diintegrasikan dengan teknik analisis stilistika isi teks. Penilaian terhadap kualitas estetis teks difokuskan pada indikator stilistika yang meliputi diksi, bahasa figuratif (majas), citraan, koherensi struktur, dan kedalaman ekspresif. Hasil penelitian menunjukkan bahwa penerapan Project-Based Learning secara signifikan meningkatkan kualitas penulisan prosa liris, terutama dalam penggunaan bahasa puitis, orisinalitas ekspresi, dan koherensi estetis. Selain itu, pendekatan yang berorientasi pada proyek mampu mendorong keterlibatan aktif, pemikiran reflektif, dan eksplorasi kreatif selama proses menulis. PjBL terbukti efektif digunakan dalam pembelajaran sastra karena urutan sintaks pembelajarannya memfasilitasi rekonstruksi bahasa dan emosi secara berkelanjutan, mulai dari penyusunan draf awal hingga tahap publikasi. Temuan ini menegaskan bahwa Project-Based Learning merupakan model pembelajaran yang efektif untuk memfasilitasi penulisan prosa liris sekaligus mendukung pengembangan kompetensi estetis dan kreatif dalam pembelajaran sastra.